On making amendments to the safety data sheet for territories - Kuzmin, A V; Gorina, L N; Demin, A (IOP conference series. Materials Science and Engineering, 2020)
The article shows the importance of developing a safety data sheet for the territories of subjects and municipalities of the Russian Federation, argues the need for risk and threat analysis of various nature and the use of information technologies in the light of general and regional informatization. An innovative approach is described, with which you can automate some stages of the development of a safety data sheet, store the characteristics of potentially dangerous technical objects, analyze the results in accordance with documents adopted by the Government of the Russian Federation. An innovative approach is described, which can be used to automate some stages of the development of a safety data sheet, store the characteristics of potentially dangerous technical objects, and analyze the results in accordance with the documents adopted by the government of the Russian Federation.